Pengembangan Soal Matematika Model PISA Menggunakan Konteks Kalimantan Timur - Hendri Prastyo (LPPM Universitas Advent Indonesia, 2020)
Education has a part in improving the quality of human resources. To have a proper quality measurement of education, there should be sustainable assessments. The Assessment could be implemented locally and world widely. Indonesia undertake the local assessments through national examinations and Indonesia also comply certain international assessments. One of the international assessment which Indonesia has complied to is PISA (Program for International Student Assessment). Meanwhile the result of PISA indicates that Indonesia is still below the average of other nation participants. There are several reasons which are being the factors for this result, one of it is students in Indonesia are not habitual to solve the problems in PISA questions. The object of this project is to analyze PISA questions and then to expand the questions by following the standards of PISA which are combined by the context of East Kalimantan. Each question is analyzed and descripted according to the level of mathematic competence, mathematic content, context used, literacy level, question format, and reviewed which are based on 2013 curriculum.